PVDF/Ni fibers synthesis by solution blow spinning technique - Dias, Y. J. [UNESP]; Gimenes, T. C. [UNESP]; Torres, S. A.P.V. [UNESP]; Malmonge, J. A. [UNESP]; Gualdi, A. J.; de Paula, F. R. [UNESP] (Springer Nature, 2018)
The development of polymeric fibers incorporated with nickel (Ni) nanoparticles (NPs) has gained broad interest due to its applications, mainly for impurities removal from oil with the aid of magnetic field. In the present study, poly(vinylidene fluoride) (PVDF) fibers containing Ni NPs were produced by solution blow spinning (SBS) technique. Scanning electron microscope (SEM) measurements showed fibers with an average diameter of 564 nm, randomly dispersed without a preferred orientation. X-ray spectrum shows peaks related to Ni showing that Ni NPs were incorporated into the fibers. The magnetic analysis of the nanocomposite shows the hysteresis loops typical of ferromagnetic behavior and ZFC–FC curves revealed the presence of superparamagnetic behaviour and an average blocking temperature of 165 K. The results achieved in this work showed that is possible to produce fibrous material, using SBS technique, with unusual magnetic properties that may be applicable in various fields, including different areas of technological industry.